Workplace conflict resolution in Wales: The unexpected prevalence of alternative dispute resolution. (August 2019) - Hann, Deborah; Nash, David; Heery, Edmund
Alternative dispute resolution (ADR) practices are increasingly being viewed as an improved way of resolving workplace conflict. Much of the empirical literature focuses on the spread of ADR amongst US organizations with little evidence of such approaches having crossed the Atlantic. This article presents new survey evidence that examines the extent to which ADR has been adopted as a strategy to resolve different forms of conflict by Welsh firms in the UK. The factors that impact upon the diffusion of ADR are also analysed. The article finds that in contrast to earlier research, ADR is widespread amongst Welsh firms, irrespective of how broadly ADR is defined. The presence of institutional actors such as specialist HR managers and recognized trade unions are found to be positively associated with more private forms of ADR.